Pengaruh Lingkungan Kerja, Budaya Organisasi dan Keterlibatan Kerja terhadap Kinerja Karyawan pada Pusat Pengembangan Sumber Daya Manusia Aparatur Perhubungan Bogor - Zepto Reyfaldo; Nor Lailla (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the effect of work environment, organizational culture, and work engagement on employee performance at the Human Resource Development Center for Transportation Officials (PPSDM) in Bogor, both partially and simultaneously. A quantitative descriptive-associative approach was used, with a saturated sampling technique applied to the entire population of 50 employees. Primary data were collected via questionnaires and analyzed using multiple linear regression in SPSS, preceded by validity, reliability, and classical assumption tests. The results show that work environment (β = -0.213; sig. 0.122), organizational culture (β = 0.326; sig. 0.066), and work engagement (β = 0.103; sig. 0.362) each had no significant partial effect on employee performance; simultaneously, the three variables also had no significant effect (F = 1.949 < F table 2.807; sig. 0.135), with an R² of 0.113 (11.3% of variance explained). These findings suggest that in a formal public-sector bureaucratic setting, employee performance is more strongly shaped by structural and administrative factors than by the organizational-behavior variables tested. Future research is recommended to incorporate additional variables such as leadership, motivation, compensation, and work discipline, with a larger sample size.